2021
DOI: 10.3174/ajnr.a7271
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Mechanical Thrombectomy in the Early (<6-hour) and Extended (≥6-hour) Time Window Based Solely on Noncontrast CT and CT Angiography: A Propensity Score–Matched Cohort Study

Abstract: BACKGROUND AND PURPOSE: Current stroke care recommendations for patient selection for mechanical thrombectomy in the extended time window demand advanced imaging to determine the stroke core volume and hypoperfusion mismatch, which may not be available at every center. We aimed to determine outcomes in patients selected for mechanical thrombectomy solely on the basis of noncontrast CT and CTA in the early (,6-hour) and extended ($6-hour) time windows. MATERIALS AND METHODS:Consecutive mechanical thrombectomies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 28 publications
(29 reference statements)
2
26
0
Order By: Relevance
“…We included 3278 patients: 2610 (79.6%) treated within 6 hours (early window), and 668 (20.4%) treated between 6 to 24 hours (late window); 141 patients had significant pre-stroke disability (mRS 3–5) and 179 patients had an NIHSS score <6 on admission; 2196 patients (67.0%) had a documented precise time of stroke onset, while the remainder were documented as last known well. Compared with the early window, patients treated in the late window were younger, had a lower baseline stroke severity (NIHSS) (median 169–20 vs 1813–22), had lower rates of IV-tPA use (33.8% vs 62.9%), were more likely to undergo general anesthesia (61.5% vs 51.5%), and were more likely to be treated using a stent retriever or a combined technique of stent retriever and thromboaspiration (table 1 and online supplemental table 1). No significant differences were observed in the remaining baseline characteristics between the two time windows.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 3278 patients: 2610 (79.6%) treated within 6 hours (early window), and 668 (20.4%) treated between 6 to 24 hours (late window); 141 patients had significant pre-stroke disability (mRS 3–5) and 179 patients had an NIHSS score <6 on admission; 2196 patients (67.0%) had a documented precise time of stroke onset, while the remainder were documented as last known well. Compared with the early window, patients treated in the late window were younger, had a lower baseline stroke severity (NIHSS) (median 169–20 vs 1813–22), had lower rates of IV-tPA use (33.8% vs 62.9%), were more likely to undergo general anesthesia (61.5% vs 51.5%), and were more likely to be treated using a stent retriever or a combined technique of stent retriever and thromboaspiration (table 1 and online supplemental table 1). No significant differences were observed in the remaining baseline characteristics between the two time windows.…”
Section: Resultsmentioning
confidence: 99%
“…Previous observational studies assessing overall rates of functional independence (mRS ≤2) in the late EVT window have reported different results at 90-day follow-up, ranging from 20% to 64% using various pre-specified clinical and imaging patient selection criteria 8–11 18 20–23. Some of these investigations incorporated perfusion-based imaging with varying adherence to the DAWN and DEFUSE-3 eligibility criteria,18 20–23 while others used solely NCCT and CTA, but also varied in their selection criteria 8–11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue has been addressed in two recent studies by Hendrix et al [10] and Nguyen et al [11] which showed that there were no significant differences in clinical outcomes in proximal anterior stroke treated with MT in the late time window between patients selected solely with simple NCCT and those selected with advanced imaging. The authors concluded that their findings have the potential to widen the indication for treating patients in the extended window using simpler, less costly, and easier to implement NCCT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study by Hendrix et al [10] as well as the multicentre international CLEAR trial (published by Nguyen et al in JAMA Neurology) [11] have shown that simple non-contrast CT (NCCT) alone may be just as useful as advanced imaging in selecting stroke patients with late-presenting LVO for MT, which could allow for a more pragmatic selection of patients in the extended window.…”
Section: Introductionmentioning
confidence: 99%